Stable Al2O3 Encapsulation of MoS2‐FETs Enabled by CVD Grown h‐BN. (29th April 2022) - Piacentini, Agata; Marian, Damiano; Schneider, Daniel S.; González Marín, Enrique; Wang, Zhenyu; Otto, Martin; Canto, Bárbara; Radenovic, Aleksandra; Kis, Andras; Fiori, Gianluca; Lemme, Max C.; Neumaier, Daniel
Abstract: Molybdenum disulfide (MoS2 ) has great potential as a two‐dimensional semiconductor for electronic and optoelectronic application, but its high sensitivity to environmental adsorbents and charge transfer from neighboring dielectrics can lead to device variability and instability. Aluminum oxide (Al2 O3 ) is widely used as an encapsulation layer in (opto)‐electronics, but it leads to detrimental charge transfer n‐doping to MoS2 . Here, this work reports a scalable encapsulation approach for MoS2 field‐effect transistors (FETs) where hexagonal boron nitride (h‐BN) monolayers are employed as a barrier layer in‐between each of the Al2 O3 and MoS2 interfaces. These devices exhibit a significant reduction of charge transfer, when compared to structures without h‐BN. This benefit of h‐BN in the gate stack is confirmed by ab initio density functional theory calculations. In addition, the devices with h‐BN layers show very low hysteresis even under ambient operating conditions. Abstract : A scalable encapsulation approach for MoS2 field‐effect transistors (FETs) based on h‐BN is investigated. h‐BN monolayers are employed as a barrier layer in between each of the Al2 O3 and MoS2 interfaces. These devices exhibit a significant reduction of charge transfer and low hysteresis even ambient operating conditions when compared to structures without h‐BN. This has been confirmed by ab initio density functional theory calculations.